The push a climber's search for the path - Caldwell, Tommy (Penguin Books, 2017)
"This engrossing memoir chronicles the journey of a boy with a fanatical mountain-guide father who was determined to instill toughness in his son to a teen whose obsessive nature drove him to the top of the sport-climbing circuit. Caldwell's affinity for adventure then led him to the vertigo-inducing and little understood world of big wall free climbing. But his evolution as a climber was not without challenges; in his early twenties, he was held hostage by militants in a harrowing ordeal in the mountains of Kyrgyzstan. Soon after, he lost his left index finger in an accident. Later his wife, and main climbing partner, left him. Caldwell emerged from these hardships with a renewed sense of purpose and determination. He set his sights on free climbing El Capitan's biggest, steepest, blankest face the Dawn Wall. This epic assault took more than seven years, during which time Caldwell redefined the sport, found love again, and became a father."--Jacket.